Lukis Tekstil Dengan Nuansa Ornamen Tradisional Pada Busana Kasual Wanita Sebagai Produk Wirausaha Seni - Kingki Yani, Made; Yugus, A.A. Gede; Putra, I Gusti Ngurah (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2022)
Seeing from the conditions in the field of painting that continues to develop from time to time, artists are now applying painting to various media to be able to maintain the selling value of their artwork. The emergence of various technologies such as print and screen printing is a challenge for painters in marketing their work. Not only canvas, nowadays painting is widely applied to daily necessities, one of which is clothing. Unique hand painting and adapting to the growing trend in fashion is a very unique attraction. In addition to adding to the value of beauty, the addition of paintings to clothing also adds to the selling value of the clothing. The addition of decoration to a garment is known as surface design. This is where the author's idea emerged to develop the author's artistic entrepreneurship product by applying a surface design in the form of a painting with traditional ornament nuances on women's casual clothing. Casual clothing with a modern style will have an elegant impression when combined with motifs from traditional Balinese ornaments. It can be concluded that, in entrepreneurship in the field of painting, artists do not have to sell their works in the form of paintings on canvas. Making daily necessities as a medium for painting is a very good opportunity for entrepreneurship in the field of art.